Analisis Status Mutu Sungai Pawan di Kabupaten Ketapang Berdasarkan Metode STORET - Haliska, Novita; Jumiati, Jumiati; Saziati, Ochih (Jurnal Teknologi Lingkungan Lahan Basah, 2026)
The Pawan Watershed (DAS Pawan) is one of the main watersheds in Ketapang Regency, West Kalimantan Province, serving as an essential water source for community needs while receiving pollutant loads from residential areas, plantations, agricultural activities, and palm oil industries. Pollution pressure increases due to the discharge of domestic wastewater, runoff from plantation areas, and various industrial activities. This study aims to identify pollution sources in the Pawan River, assess its water quality, and analyze its status using the STORET method. This research is a quantitative descriptive study that provides an overview and explanation of pollution sources, water quality characteristics, and the water quality status of the Pawan River. The data used in this study are secondary data obtained from the Environmental and Forestry Agency of West Kalimantan Province for the period 2021-2024, covering 10 monitoring points. The analyzed water quality parameters include pH, TSS, BOD, COD, DO, nitrate, phosphate, and fecal coliform, in accordance with the Class II water quality standards set out in Government Regulation No. 22 of 2021. The results of the inventory indicate that pollution sources originate from residential activities and palm oil industries (point sources) as well as plantations and fields (non-point sources). The highest recorded values were 12,9 mg/L for BOD in Semester II, 125 mg/L for COD in Semester I, and 0,3 mg/L for phosphate in Semester II, all of which exceeded the water quality standards. Based on the STORET method, the water quality status of the Pawan River is heavily polluted at monitoring point X, with a score of -34 in Semester II.